Understanding of Loyalty Programs’ Participation Rules - de Lima, Lunie Imamura (2013)
The understanding of loyalty programs’ participation rules is tested in this study within three experiments conducted to check the influence of the regulatory focus, prize type, and of the interaction of both. Experiment 1 shows that the regulatory focus somehow affects the degree of understanding of the programs’ rules. Experiment 2 shows that the prize type also affects the degree of understanding of the programs’ rules. And, at last, it is shown that Experiment 3 does not corroborate the hypothesis of the interaction of those variables on the degree of understanding of the programs’ rules. The conclusion is that the understanding of loyalty programs’ rules is higher to individuals in the state of prevention and of receiving utilitarian award, and that, however, there is no influence of their interaction. The study contributes to corroborate the matching effect and the hypotheses of the regulatory focus theory on the consumer behavior, also proposing managerial implications to loyalty programs’ managers.